Comments on "Experimental assessment of the thermodynamic factor for diffusion in CoCrFeNi and CoCrFeMnNi high entropy alloys". (November 2019) - Belova, Irina V.; Murch, Graeme E.
Abstract: In this contribution, as comments to the paper in Scripta Materialia, v.157, p.81, 2018, we show that the pseudo-binary approach for analysis of interdiffusion in multicomponent alloys has its reference value of the Manning factor (vacancy-wind factor) that is very different from true binary interdiffusion. In true binary interdiffusion, this factor is usually compared with unity. In the pseudo-binary analysis this reference value must be changed to the inverse of N 1  +  N 2, where N i are the compositions (mole fractions), and components 1 and 2 are the atomic components that have different terminal compositions in the corresponding experiment.